Perancangan Sistem Aplikasi Penggajian Pegawai Dalam Rangka Efisiensi Reformasi Birokrasi: Studi Kasus Di Kementerian Perdagangan RI - Nori, Agung Seska (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2019)
Technology is created for helping human’s activity to become easier, including for activities in an office. The growth of the information technology has followed by growth of the computer technology as its proponent. Computer has high grade accuracy in processing data. By an information technology, human can process data become faster and easier. In this research, an employee payroll application system was created the Ministry of Trade of the Republic of Indonesia. The aim was to simplify the payroll process and organize payroll reporting process. The method that was used in this research is grounded research. Software used in this research are Java (Netbeans IDE version 8.0), MySQL 5.5.32, and XAMPP 3.2.1. The system development method to create a payroll information system was the waterfall method. The results of the study is a payroll application system with output in the form of employee reports, attendance reports, detailed salary reports, payroll reports, and pay slip reports.